2017
DOI: 10.1371/journal.pone.0169152
|View full text |Cite
|
Sign up to set email alerts
|

Subfoveal Choroidal Thickness in Central Serous Chorioretinopathy: A Meta-Analysis

Abstract: PurposeTo evaluate the relationship between subfoveal choroidal thickness (SFCT) and eyes with central serous chorioretinopathy (CSC) versus fellow or control eyes.MethodsWe performed a meta-analysis using databases including PubMed, Embase and ISI Web of Science to find relevant studies. Weighted mean difference (WMD) was calculated for the SFCT in CSC eyes, the unaffected fellow eyes and normal controls.ResultsTwelve studies were selected for this meta-analysis, including 1108 eyes (397 CSC eyes, 228 unaffec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
2
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 43 publications
(57 reference statements)
3
25
2
2
Order By: Relevance
“…29,30 Similarly, findings from a metaanalysis of studies among CSCR patients revealed SCT values to range from 414 AE 109.0 to 61.4 AE 101.4 μm in the affected eyes and from 350.9 AE 116 to 387 AE 94 μm in the control eyes. 31 In our study, there was no significant correlation between SCT and visual acuity either at baseline or following spontaneous resolution. Similarly, in a study by Yalcinbayir et al, 4 the authors reported no significant association between SCT and visual acuity in patients with CSCR and emphasised the likelihood of choroidal thickness not to be among the primary determinants of visual acuity, despite its important role in the pathophysiology of CSCR.…”
Section: Discussioncontrasting
confidence: 63%
“…29,30 Similarly, findings from a metaanalysis of studies among CSCR patients revealed SCT values to range from 414 AE 109.0 to 61.4 AE 101.4 μm in the affected eyes and from 350.9 AE 116 to 387 AE 94 μm in the control eyes. 31 In our study, there was no significant correlation between SCT and visual acuity either at baseline or following spontaneous resolution. Similarly, in a study by Yalcinbayir et al, 4 the authors reported no significant association between SCT and visual acuity in patients with CSCR and emphasised the likelihood of choroidal thickness not to be among the primary determinants of visual acuity, despite its important role in the pathophysiology of CSCR.…”
Section: Discussioncontrasting
confidence: 63%
“…Choroidal imaging of almost all eyes with active CSCR as well as some asymptomatic fellow eyes shows subfovealchoroidal thickening and dilated choroidal vessels. [ 72 ] Chronic CSCR is believed to be part of the pachychoroid spectrum. Other features described include thinning of the inner choroidal vessels, focal choroidal excavation[ 73 74 75 ] (defined as a macular lesion with choroidal excavation detected on SD-OCT without evidence of scleral ectasia or posterior staphyloma), and loculation of fluid in the posterior choroid.…”
Section: Optical Coherence Tomography In Conditions Causing Serous Dementioning
confidence: 99%
“…Also, choroidal thickness is abnormal in conditions, such as glaucoma, 5 diabetic retinopathy, 6 amblyopia, 7 and central serous chorioretinopathy. 8 Thus, it is involved in several visual disorders, but sparse information exists on the normal changes in choroidal thickness through life. Only within the most recent decade has means of in vivo quantification of choroidal thickness been available 9 and most of the current data are limited to cross-sectional studies.…”
mentioning
confidence: 99%